"A Face Like This Is Hard to Beat": Negotiating Lilith in the Postfeminist Media Economy. Issue 2 (3rd April 2022) - Tink, Courtney; Lauwrens, Jenni
Abstract: From mythology, history, and religion to contemporary popular culture, Lilith has been represented in a variety of ways. As either an avenging vampire or a seductive temptress, or a fascinating combination of both, she has been understood as both an object of a patriarchal view of women and a liberated and liberating feminist icon. The meanings that are ascribed to Lilith are thoroughly interwoven with contemporary feminist discourse. We argue that it is precisely within the postfeminist media economy that the meanings and functions of various tropes of femininity are destabilised and renegotiated. In this article, we limit our focus to the appearance of Lilith in two recent television series, namely The Chilling Adventures of Sabrina (2018–) and Shadowhunters (2016–2019). Our aim is to highlight the ways in which the Liliths represented in each series negotiate one specific trope of femininity used in popular culture, namely the femme fatale. We show that whilst these manifestations of Lilith as postfeminist femme fatale may open up potentialities for feminist resistance, they are simultaneously trapped in an oppressive system of representation that constructs women as passive objects of heteronormative male fantasies.